Influence of compaction on the properties of remoulded cemented sands - REDDY, POLAMURI RAMA MOHAN; SAILESH, BANTU (The journal of contemporary issues in business and government, 2019)
Both in-depth laboratory analysis and scale models were used to investigate the characteristics and behaviour of compacted cemented sands in Kuwait. While being dug up, the cementation bonds are broken and the catch, as it is called in the area, is changed into clayey sands with a high percentage of particles (anywhere from 20% to 40%). All the fundamentals were checked: basic characteristics, compaction, permeability, direct shear, and consolidation. A circular plate was also loaded to failure in model testing on compacted soils. The relative compaction of the test soil was 85%, 90%, 95%, and 100%. Results show that when relative compaction is reduced from 100% to 85%, the ultimate bearing capacity and the shear strength parameters c, decline significantly, while the compressibility parameters Cc, Cs, and the permeability rise. Rates of change in a number of soil characteristics are analysed as a function of relative compaction.